Competing against COVID-19: what about the mental health problems of athletes with disabilities? - Denerel, Nevzad; Lima, Yavuz (Taylor & Francis Ltd, 2022)
Objectives Although there is growing interest in athletes' mental health (MH), there is a paucity of research exploring MH in athletes with disabilities (AWD). The purpose of this study was to evaluate the impact of the COVID-19 pandemic on the psychological state of AWD. Materials and Methods An online survey including demographic questions, SARS-CoV-2-related questions, and standardized scales assessing depression, anxiety, stress, coronavirus anxiety (CAS), and nonspecific psychological distress was distributed to AWD. Results A total of 362 athletes (183 AWD) participated in the study (response rate 31.2%). AWD infected with SARS-CoV-2 reported higher depression, anxiety, and CAS scores than AWD not infected with SARS-CoV-2 (Z = -2.10, ES = 0.15 Z = -3.45, ES = 0.25; Z = -2.43, ES = 0.18; respectively). Female AWD reported higher anxiety scores compared to males (Z = -2.25, ES = 0.16). Depression (Z = -2.80, ES = 0.20), stress (Z = -2.12, ES = 0.15) and K-10 (Z = -2.02, ES = 0.14 scores of individual sport AWD were higher than team sports AWD. Conclusion MH problems in AWD were associated with a wide range of variables such as being infected with SARS-CoV-2, female gender, competing in an individual sport, and having performance concerns. In light of these results, MH assessment should be undertaken for AWD to ensure appropriate and timely intervention.
Keywords: Psychological state; Disabled athletes; Paralympics; SARS CoV-2; Sports medicine